Press Release (Tufts Archival Research Center, 2005)
This document is about the agreement of twenty-three political parties agreeing to a unified Code of Conduct under the auspices of the African Union. High-Level Implementation Panel. This Code of Conduct will be applied by during the two referenda and the , and the popular consultation to be held afterwards.